Kepemimpinan Kepala Madrasah Dalam Peningkatan Profesionalisme Guru Di MTs Sunan Gunung Jati Gurah Kediri - Ardiansah Ardiansah; Hani Adi Wijono (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
The purpose of this study (1) to describe the professionalism of teachers at MTs Sunan Gunung Jati Gurah Kediri. (2) Describe the strategy of the Head of Madrasah in increasing teacher professionalism at MTs Sunan Gunung Jati Kediri. (3) Describe the factors supporting and inhibiting the leadership of the Madrasah Head in increasing teacher professionalism at MTs Sunan Gunung Jati Gurah Kediri. This research approach uses qualitative methods, namely observations, interviews, and document review. And the results of this study are (1) the professionalism of teachers at MTs Sunan Gunung Jati Gurah Kediri, including; there is a high commitment and sense of responsibility, mastery of the material to be taught, and implementing the existing code of ethics. (2) The strategy of the Head of Madrasah in increasing teacher professionalism at MTs Sunan Gunung Jati Gurah Kediri, including; the existence of teacher selection, teacher performance coaching, supervision of teacher performance, coaching education staff discipline, and providing motivation. (3) Factors supporting and inhibiting the leadership of the Madrasah Head in increasing teacher professionalism at MTs Sunan Gunung Jati Gurah Kediri, including; the supporting factors are the cohesiveness, and the teacher's awareness of the mandate carried. As for the inhibiting factors, the first is the limitation of the Head of Madrasah in nurturing teachers, especially those who are older than him. And the last is the limited facilities and infrastructure that are not yet adequate.